Rancang Bangun Sistem Informasi KKN LPPM UPN “Veteran” Jawa Timur Berbasis Web Menggunakan Metode Rapid Application Developmet - Anggoro, M. Novianto; Wibowo, Nur Cahyo; Kartika, Dhian Satria Yudha (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UPN “Veteran” Jawa Timur plays an active role in organizing research and community service activities. One of its main programs is the Kuliah Kerja Nyata (KKN). Currently, the management of KKN activities lacks a system that supports the business processes involved. The registration and submission of outputs are still done using Google Forms, and there is no system for digitizing certificates. Therefore, the